Bone marrow mesenchymal stem cell-derived exosomal microRNA-335 alleviates vascular calcification by targeting SP1 - Li, Yaodong; Chen, Chuanzhen; Kong, Jingbo; Huang, Junjie; Liu, Liguo; Liu, Cunfa; Dai, Bing; Huang, Mei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundVascular calcification (VC) is a critical pathological characteristic of cardiovascular diseases like atherosclerosis, frequently linked to phenotypic alterations in vascular smooth muscle cells (VSMCs) and the activation of bone-forming genes. Exosomes derived from bone marrow mesenchymal stem cells (BMSCs) have been shown to significantly attenuate VSMC calcification.MethodsTo investigate whether BMSC-derived exosomes mitigate VSMC calcification through microRNAs (miRNAs) regulation, we developed an in vitro model using β-glycerophosphate-induced calcification and an in vivo model using vitamin D3-induced calcification. Exosomes were extracted from BMSC culture media via ultracentrifugation and analyzed using transmission electron microscopy and particle size distribution assays.ResultsFunctional and phenotypic assessments revealed that BMSC-derived exosomes markedly reduced VSMC calcification. RT-qPCR analysis further indicated that BMSC-derived exosomes regulate VSMC calcification by modulating rno-miR-335 (miR-335). The miR-335 mimic notably suppressed the expression of the osteogenic regulator RUNX2 in VSMCs. Dual-luciferase reporter assays demonstrated that SP1 is a direct target of miR-335. Exosomal miR-335 inhibited SP1 expression, resulting in reduced mRNA and protein levels of RUNX2. In vivo studies confirmed that agomiR-335 treatment significantly lowered SP1 levels in the aorta of male SD rats, alleviating vitamin D3-induced VC.ConclusionThis study highlights that BMSC-derived exosomes regulate VC via the miR-335/SP1 axis, offering novel molecular targets for treating VC.